Free Software on High School Teaching-Learning Process in Ecuador - Basurto Velez, Manuel Antonio; Bailón, Geovany Benavides (International Journal of Psychosocial Rehabilitation, 2020)
The use of software in educational processes has proven to be a valuable tool in the teaching-learning process, however the use of proprietary software has greatly diminished its potential due to access difficulties in educational systems, where investment for the provision of computer licenses it is little, in addition to conditioning educational processes on software with closed codes, it represents a very limited option because these do not allow improvements or adaptations to be adapted to new situations, in this sense This work seeks expose how free software can positively impact education at the baccalaureate levels, showing the usefulness in supporting the teaching-learning process. To carry out this research, a systematic review of the literature was carried out, regarding the mechanisms together with the most generalized support tools in the use of educational processes, in order to subsequently generate a valid proposal for increasing motivation and performance in students in different areas.